The Role of Village Head Leadership in Improving Employee Performance - Nursahidin, Nursahidin; Nabila, Nurin; Putri, Abni Syaifulla; Sutarjo, Moh (Jurnal Polisci, 2025)
Background. Leadership is key to the success of any organization, including village administration. The village head plays a strategic role in improving employee performance. Gintung Lor Village in the Susukan District of Cirebon Regency faces several leadership and employee performance issues, including a lack of coordination between the village head and employees, a high proportion of employees with low educational backgrounds, and inadequate training to enhance employee competence. Aims. This study aims to analyze the role of the village head in improving employee performance in Gintung Lor Village. Methods. The study employs a descriptive qualitative method, collecting data through observation, in-depth interviews, documentation, and a literature review. Result. The results indicate that the village head plays a crucial role in enhancing employee performance and fostering public trust in the village government and its development. Implementation. However, obstacles to performance remain, so efforts are needed to improve coordination between the village head and employees, enhance employees' education and competencies, and conduct training to improve their skills.